After the firmitas. A metabolist prespective of resilient architecture - Zeila Tesoriere (Agathón)
Architecture has been built for millennia to stay the same – according to the Vitruvian firmitas. Instead, today it is oriented toward a dynamic adaptation to the changes in its context. The climate change is the most evident epiphenomenon among those that have imposed the new paradigms of resilience, the programmatic indeterminacy, the morphological flexibility, the open systemic approaches. Far from being a simple technical adaptation to new needs, the resilient architecture progressively clarifies its theoretical assumptions and its cultural derivations. A genealogical approach concerning the reformulation of some themes firstly introduced by Japanese Metabolism, helps to reframe its evolution and aims to contribute to the understanding of the formal definition of these new architectures.